2015
DOI: 10.1080/17445302.2015.1037678
|View full text |Cite
|
Sign up to set email alerts
|

Residual strength of corroded subsea pipelines subject to combined internal pressure and bending moment

Abstract: Subsea pipelines used for oil and gas production in deepwater are exposed to harsh environment involving corrosion, high internal pressure, high temperature, and bending moment. Failure of subsea pipelines can cause serious problems, including oil/gas spill, hydrocarbon explosion and fires, production downtime, and maintenance and repair. Hence, it is of paramount importance to prevent failure of subsea pipelines. The aim of the present study is to investigate the residual strength characteristics of corroded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Experimental and numerical studies were performed to understand the behaviour of tubular members with artificially introduced localized pitting or patch-type corrosion, which are applied in steel lined pipes [10,11] and tubular members for offshore structures [12,13]. Recent experimental research into the effect of pitting corrosion artificially drilled on the local region of tubular members for offshore platforms [14] showed that aside from the compressive strength, pitting corrosion affects the structural failure mode in the pattern of local buckling.…”
mentioning
confidence: 99%
“…Experimental and numerical studies were performed to understand the behaviour of tubular members with artificially introduced localized pitting or patch-type corrosion, which are applied in steel lined pipes [10,11] and tubular members for offshore structures [12,13]. Recent experimental research into the effect of pitting corrosion artificially drilled on the local region of tubular members for offshore platforms [14] showed that aside from the compressive strength, pitting corrosion affects the structural failure mode in the pattern of local buckling.…”
mentioning
confidence: 99%
“…Considerable research such as Yeh and Kyriakides (1986), Yeh and Kyriakides (1988), Park and Kyriakides (1996), Vitali et al (2005) and Mohd et al (2015) has been conducted on the residual ultimate strength of offshore metallic pipelines. Critical parameters that would affect the pipeline strength include the diameter-to-thickness ratios (D/t), length-to-diameter ratios (L/D), material properties, load conditions, manufacturing processes, initial imperfections and residual stress.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, an incorrect prediction of water distribution leads to significant mistakes in predicting the corrosion rate. Moreover, selecting an appropriate type of inhibitor and estimating the required amount of inhibitor and corrosion resistant materials require a prior knowledge of water distribution inside the pipe (Niborg, 2005;Nesic, 2007;Cai et al, 2012;IIman and Kusmono, 2014;Mohd et al, 2015;Papavinasam et al, 2010).…”
Section: Introductionmentioning
confidence: 99%